Biochemical, microbiological and technological characteristics of type II sourdoughs produced with lactic acid bacteria single-strains - Siepmann, Francieli Begnini; Almeida, Beatriz Sousa de; Gomes, Tatiane Aparecida; Waszczynskyj, Nina; Spier, Michele Rigon (Semina: Ciências Agrárias, 2022)
The interplay between biochemical characteristics and the generation of volatile compounds in 11 type II sourdough fermented by single strains of lactic acid bacteria (LAB) was studied. Samples were collected at 0, 6, 9, 12, 15, 18 and 24h for analyses of microbial growth, pH, titratable acidity and CO2 production. During the first 12h, the LABs entered the stationary phase, and the formation of organic and carboxyl acids, alcohols, and esters were observed. Although acidity is an important characteristic of sourdough, in this work increasing the acetic acid content decreased yeast growth and the CO2 retention capacity of the doughs. The main carbohydrate consumed by autochthonous yeast was influenced by the LAB added (homo-or heterofermentative), as observed by correlation analysis. Maltose and glucose showed a strong and negative correlation with the yeast cell density in the dough fermented by homo and heterofermentative LAB, respectively. Moreover, LAB had an important effect on the aromatic profile, being the alcohols, aldehydes, alkanes, organics acids and esters mainly groups characterized. Altogether, 100 different volatile compounds were identified; however, each dough had a different volatile profile. This study shows, for the first time, the influence of a single strain of LAB on the characteristics of type II sourdough.